Televisions : Kunst sieht Fern. - Abetz, Maike; Auder, Michel; Baldessari, John; Beck, Martin; Bennett, Mark; Birnbaum, Dara; Blair, Dike; Brea, Josè Luis; Breitz, Candice; Bronson, AA; Calderón, Miquel; Cattelan, Maurizio; et al. (Wien : Kunsthalle Wien, 2001)
Abetz, Maike ; Drescher, Oliver ; Acconci, Vito ; Ant Farm ; Apsolutno ; Art Club 2000 ; Auder, Michel ; Baldessari, John ; Beck, Martin ; Bennett, Mark ; Bickerton, Ashley ; Birnbaum, Dara ; Blair, Dike ; Breitz, Candice ; Burden, Chris ; Calderon, Miguel ; Calle, Sophie ; Cattelan, Maurizio ; Charlesworth, Sarah ; Clark, Larry ; Dany, Hans-Christian ; Schäfer, Christoph ; Demand, Thomas ; Diamond, Jessica ; Dibbets, Jan ; Do-Foundation ; Dombrowe, Peter ; Emin, Tracey ; Farocki, Harun ; Ujica, Andrei ; Gala Committee ; General Idea ; Goldin, Nan ; Graham, Paul ; Grennan, Simon ; Sperandio, Christopher ; Haring, Keith ; Herrmann, Astrid ; Hill, Christine ; Horowitz, Jonathan ; Isermann, Jim ; Ivekovic, Sanja ; Jankowski, Christian ; Kippenberger, Martin ; Kluge, Alexander ; Kruger, Barbara ; Landers, Sean ; Lawler, Louise ; LOT/EK ; Manetas, Miltos ; Margreiter, Dorit ; McCollum, Allan ; Miller, John ; Muntadas, Antoni ; Oursler, Tony ; Paik, Nam June ; Paper Tiger Television ; Parreno, Philippe ; Zhang, Peili ; Pettibon, Raymond ; Pflumm, Daniel ; Prince, Richard ; Reeb, David ; Rehberger, Tobias ; Rist, Pipilotti ; Rockenschaub, Gerwald ; Rogg, Ursula ; Rosefeldt, Julian ; Rosler, Martha ; Schlingensief, Christoph ; Segalove, Ilene ; Serra, Richard ; Shrigley, David ; Simmons, Laurie ; Smith, Michael ; White, Joshua ; Solomons, Doron ; Staehle, Wolfgang ; Steinbach, Haim ; Szuper Gallery ; TVTV ; Van Gogh T.V. ; Bruch, Klaus vom ; Weems, Carrie Mae ; Wegman, William ; Westphalen, Olav ; Wrange, Mans ; Zehrer, Joseph
Televisions : Kunst sieht Fern, Kunsthalle Wien, 18.10.2001 - 06.01.2002
Duits
kunstcatalogus